Leveraging an Innovation Model to Facilitate ICD-11 Implementation. - Giannangelo, Kathy L.; Pine, Michael B.; Tompkins, Christopher P. (Perspectives in Health Information Management)
The 11th Revision of the International Classification of Diseases (ICD-11) with its informaticsbased infrastructure has transformed an antiquated classification system into a suite of 21st century computer applications. This manuscript proposes an innovation model to facilitate the implementation of ICD-11 by the US. The model introduces ICD-11 Comprehensive Clinical Linearization, Evolution and Response, or C-CLEAR, a fully coded comprehensive clinical linearization and syntactical rules for combining these codes. These enhancements can be incorporated into electronic coding tools that enable clinical reporters to transmit complex clinical concepts expressed in detailed natural clinical language by means of standardized clusters of ICD-11 stem and extension codes. The model can support rich clinical data captures such as condition acuity and severity, as well as pharmacological treatments. This approach shows promise to accelerate ICD-11 implementation with minimal disruption and maximal net benefits but will require vetting, testing and input from expert stakeholders.